Do Bond Investors Care About Engagement Auditors’ Negative Experiences? Evidence from China - Gong, Guangming (Journal of business ethics, 2019)
Using data from China, where the identity of engagement auditors is disclosed, we find significant relationships between engagement auditors’ negative experiences and the costs of corporate bonds. Further tests differentiate field and review auditors’ experiences, and we find that both field and review auditors’ negative experiences are significantly related to higher costs of corporate bonds. In addition, we find that the above results are significant only when the engagement auditors are affiliated with non-Big10 audit firms. Using path analysis, we find that credit rating is a possible channel through which information on engagement auditors’ negative experiences can transfer to bond investors. Regarding non-price terms, we conclude that engagement auditors with negative experiences are associated with smaller bond sizes, shorter bond maturities, a higher likelihood of requiring collateral, and more restrictive covenants. Further analyses also show that the effects of engagement auditors’ negative experiences on the costs of corporate bonds are less pronounced for well-governed firms. To show that our results obtained from China’s corporate bond market are relevant to loan markets, we replicate the above tests using a Chinese sample, and the results from the loan market are consistent with those from the corporate bond market. Overall, our empirical results suggest that investors are indeed concerned with engagement auditors’ negative experiences.